2020
DOI: 10.1021/acsabm.0c00400
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Samarium-Coated Magnesium Implants for Immunocompromised Patients

Abstract: The removal of tumors in the osseous tissue leads to functional disorders. To overcome this issue, biodegradable implants are used to replace the damaged part of the system. In the study, samarium oxide was coated on the anodic layer of AZ31 magnesium alloy. The potentiodynamic polarization, electrochemical impedance, and localized electrochemical impedance spectroscopy studies were carried out for the samarium-coated magnesium alloy. The corrosion resistance of the coating improved several folds than the bare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…These results are in good agreement with other similar studies regarding the potential antimicrobial activity of samarium ions or samarium based composites [27,29,[53][54][55][56][57][58]. Moreover, the quantitative assays were in good agreement with the results obtained in the qualitative studies performed on 5Sm-HAp suspension, target and coatings.…”
Section: Resultssupporting
confidence: 91%
“…These results are in good agreement with other similar studies regarding the potential antimicrobial activity of samarium ions or samarium based composites [27,29,[53][54][55][56][57][58]. Moreover, the quantitative assays were in good agreement with the results obtained in the qualitative studies performed on 5Sm-HAp suspension, target and coatings.…”
Section: Resultssupporting
confidence: 91%
“…Ying L. and collaborators, in their study entitled "Long-term biodistribution in vivo and toxicity of radioactive/magnetic hydroxyapatite nanorods", showed that Sm-HA:Gd nanorods exhibit an excellent γ-emission, relaxivity and biocompatibility thus making them suitable for potential applications in the biomedical area (including single-photon emission computed tomography (SPECT) and magnetic resonance imaging (MRI) [17]. Moreover, according to previous studies, the presence of lanthanide ions on surface of the magnesium alloys induces a superior corrosion resistance, anticancer and antimicrobial activity [16]. The interaction between the implant surface and the surrounding tissue is essential and thus it becomes imperative to obtain coatings with improved biological and antimicrobial properties and finally high-performance implants [18].…”
Section: Introductionmentioning
confidence: 88%
“…Recent studies, have also shown that the biological activity of samarium doped hydroxyapatite (SmHAp) it is strongly influenced by the amount of Sm 3+ that is found in the samples [10][11][12][13][14]. Moreover, has been highlighted that the presence of Sm 3+ in various biomaterials, used in the medical field, increases their anticancer activity [15,16]. Ying L. and collaborators, in their study entitled "Long-term biodistribution in vivo and toxicity of radioactive/magnetic hydroxyapatite nanorods", showed that Sm-HA:Gd nanorods exhibit an excellent γ-emission, relaxivity and biocompatibility thus making them suitable for potential applications in the biomedical area (including single-photon emission computed tomography (SPECT) and magnetic resonance imaging (MRI) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in their recent work, Kannan et al [19] highlighted that the presence of a samarium oxide coating on a Mg implant could prevent on the one hand the recurrence of bone tumors and metastases and on the other hand the appearance of post-implant infections.…”
Section: Introductionmentioning
confidence: 99%